IDIOMATIC PHRASES IN MARRIAGE SPEECH OF HELONG TRIBUTE CUSTOMS AS AN ENRICHMENT OF TEACHING MATERIALS FOR SEMANTIC LECTURES - Kosmas, Jeladu; Kosat, Paulina Maria Yovita; Pekuwali, Dian Sari Arinda; Robot, Marselus (Pendidikan Bahasa dan Sastra Indonesia Universitas Nusa Cendana, 2024)
The aim of this research is to describe idiomatic phrasesin the traditional marriage story of the Helong tribe as enrichment of teaching materials for semantics courses. The theoretical basis used in this research is idiomatic phrasesstated by Keraf (2000), namely (2) Idiomatic based on its type (2) Idiomatic based on its form. Using a qualitative approach and the method and collection technique used in this research is the observation method with three techniques, namely (1) skillful listening and involvement method, (2) recording technique, and (3) note taking. Other methods used are the questionnaire method and the note-taking method. The research results show that there are four stages, namely (1) stagekeket kodale'ask; (2) levelHilli Hleken'come in and ask'; (3) levelfog wrap'enter marriage or bring dowry'; (4) levelkait tamang in mule te'between'. In these four levels there are 13 idiomatic phrase data.